Pengaruh Model Pembelajaran TGT (Teams Games Tournament) Modifikasi Metode Gasing Terhadap Hasil Belajar Matematika Siswa - Rahmi Diah; Nurdiana Siregar (LP. Ma'arif Janggan Magetan, 2023)
The purpose of this study was to find out whether there is an effect of the modified GASING method TGT (Teams Games Tournament) learning model on the mathematics learning outcomes of third grade elementary school students. The research method used in this research is a quantitative approach with the type of pre-experimental research with a one group pretest-posttest design. The independent variable in this study is the influence of the TGT learning model modified by the GASING method, while the dependent variable is the result of learning mathematics. The population of this study were third grade students at SD Muhammadiyah 06 Medan in the 2022/2023 academic year. The sample used is a total sample of 19 people. Data collection techniques were carried out using tests that were given twice, namely pretest and posttest. The instruments used in this study were lesson plans and multiple choice questions which had been validated qualitatively by two expert lecturers in their fields. Data analysis techniques used the normality test, the Wilcoxon non-parametric test, and the Normality Gain (N-Gain) test. The results of this study found that there was an effect of the modified TGT learning model of the GASING method on the mathematics learning outcomes of class III students as evidenced by the students' mathematics learning outcomes before being given treatment which was 56.84 then after being given treatment it increased to 80.00. The results of the Wilcoxon test show that the significance value (sig) is smaller than α, namely 0.000 <0.05, which means is accepted and is rejected. The effect of applying the modified TGT learning model to the GASING method is also evident from the increase in learning outcomes as evidenced by the N-Gain (g) test results obtained by 0.6241 included in the medium category.